Removal of Depleted Uranium from Water Using Titanium Dioxide - Wazne, Mahmoud (2017)
Groundwater contamination with depleted uranium (DU) is a concern in many areas where uranium mining or uranium processing and recycling have occurred. Uranium typically migrates with groundwater as uranyl carbonates and uranyl hydroxides complexes. Soluble U(VI) has been found to strongly adsorb onto the reactive surface of nanocrystalline titanium dioxide. This presentation addresses the formation of a chemically reactive barrier by injecting TiO2 adsorbent into a sand column. Tests were performed at varying influent concentrations and flow rates. Optimal conditions for homogeneous TiO2 distribution in the sand column were determined and used to saturate a column with adsorbent. A second influent of contaminated groundwater was subsequently passed through the sand column and the U distribution in the effluent was monitored.